Criminal responsibility for the commission of extremist crimes - Лихова, Софія Яківна; Лобода, Юлія Валентинівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article deals with the problem of criminal responsibility for the commission of extremist crimes, noted that it is necessary to legislate the definition of «extremism» and the derived concepts. Ways of preventing and preventing extremism are suggested. During many years the problem of extremism has been relevant in every corner of the world, but, unfortunately, in many countries there is no liability, in particular, criminal responsibility, for carrying out extremist actions.In Ukraine, the concept of «extremism» or «extremist activity» is not regulated in the legislation. The aim of the article is to argue the need to institute an institution of criminal responsibility for extremism on the territory of Ukraine, to consolidate the definition of «extremism» and derivative concepts in criminal legislation, to identify signs and forms of extremist activity, and to provide suggestions for the prevention and prevention of this dangerous phenomenon.Extremism is not a single crime, for example, a murder committed on the basis of religious or racial intolerance, but a complex crime that consists of several episodes united by one goal. Sometimes it is difficult to distinguish between terrorism and extremism, they have one goal – criminal influence on the population of the country, maintaining a state of constant hostility, making political demands, causing or threatening harm to the person, property, the interests of society and the state.The question of fixing the definition of extremism and determining its features is important, because it will allow us to work out the main directions of combating this phenomenon and determine the state policy of countering extremism and the like. A new culture of discourse must be formed in Ukraine, which takes into account the needs and values of various social groups. It is also necessary to provide a platform and tools for broad social dialogue, the introduction of alternative methods for solving problematic issues.